The distinct and overlapping phenotypic spectra of FOXP1 and FOXP2 in cognitive disorders - Bacon, Claire; Rappold, Gudrun (Human genetics, 2012)
Rare disruptions of FOXP2 have been strongly implicated in deficits in language development. Research over the past decade has suggested a role in the formation of underlying neural circuits required for speech. Until recently no evidence existed to suggest that the closely related FOXP1 gene played a role in neurodevelopmental processes. However, in the last few years, novel rare disruptions in FOXP1 have been reported in multiple cases of cognitive dysfunction, including intellectual disability and autism spectrum disorder, together with language impairment. As FOXP1 and FOXP2 form heterodimers for transcriptional regulation, one may assume that they co-operate in common neurodevelopmental pathways through the co-regulation of common targets. Here we compare the phenotypic consequences of FOXP1 and FOXP2 impairment, drawing on well-known studies from the past as well as recent exciting findings and consider what these tell us regarding the functions of these two genes in neural development.